2009
DOI: 10.1111/j.1095-8649.2009.02294.x
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and genetic seasonal dynamics of European eel Anguilla anguilla recruitment in southern France

Abstract: The fine scale morphological and genetic dynamics of successive waves of Anguilla anguilla glass eel recruitment was studied over a 2 year period at a southern European Mediterranean location (Camargue, France) with continuous recruitment. Using morphometric [total length (L(T)), mass (M), condition (K) and pigmentation stage] as well as genetic (allozyme) markers, the aim was to test for the existence of temporally separated spawning groups and explore the relation between genetic variability and morphologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 56 publications
1
9
0
Order By: Relevance
“…However, western Atlantic glass eels show no marked differences in size or in pigmentation stages among locations in Portugal, Spain, France and Ireland although Boëtius & Boëtius (1989) noted that pigmentation stages varied widely with no obvious temporal pattern among several northern Atlantic locations. Studies available for the Mediterranean [La Camargue, southern France (Maes et al, 2009) and Río Arno, northeastern Italy (Gandolfi et al, 1984)] also suggested temporal replacement of pigmentation stages with an increased predominance of more pigmented individuals as the season progressed and interestingly, an overall predominance of more pigmented stages than in the Atlantic glass eels (Table 4). Nonetheless, relative to the whole-season predominance of stage V B in the Iberian Ríos Nalón and Minho, in the Mediterranean Río Arno where pigmentation stages are well documented (Fig.…”
Section: Comparison With Other Locationsmentioning
confidence: 83%
See 1 more Smart Citation
“…However, western Atlantic glass eels show no marked differences in size or in pigmentation stages among locations in Portugal, Spain, France and Ireland although Boëtius & Boëtius (1989) noted that pigmentation stages varied widely with no obvious temporal pattern among several northern Atlantic locations. Studies available for the Mediterranean [La Camargue, southern France (Maes et al, 2009) and Río Arno, northeastern Italy (Gandolfi et al, 1984)] also suggested temporal replacement of pigmentation stages with an increased predominance of more pigmented individuals as the season progressed and interestingly, an overall predominance of more pigmented stages than in the Atlantic glass eels (Table 4). Nonetheless, relative to the whole-season predominance of stage V B in the Iberian Ríos Nalón and Minho, in the Mediterranean Río Arno where pigmentation stages are well documented (Fig.…”
Section: Comparison With Other Locationsmentioning
confidence: 83%
“…On the other hand, the larger size of Atlantic glass eels compared with the smaller Mediterranean individuals may be caused by a greater osmotic exchange cost in the markedly higher-salinity Mediterranean Sea. Nevertheless, a remarkable heterogeneity and a large proportion of the variance unexplained (*75%) may result from genetic heterogeneity (Maes et al, 2009) but still suggests that environmental factors such as water temperature and salinity may affect the pigmentations stages (Briand et al, 2005) and should be taken into account in future investigations on glass eel recruitment.…”
Section: Discussionmentioning
confidence: 98%
“…Seasonality in mean body length (left) and body condition (right) of glass eels recruiting to western Portugal (1994–2001, open circles), in comparison to published values from France (large closed circles: Atlantic—Guerault et al., ; Desaunay & Guerault, ; small closed circles: Mediterranean—Maes et al., ). Lines and grey shades result from GAM .…”
Section: Resultsmentioning
confidence: 96%
“…These studies evidenced that temporal genetic differences between groups of glass eels recruited at the same site within the same year (also referred to as glass eel waves) can exceed between-site large-scale spatial genetic differences of the same recruitment cohort (Maes et al 2006, 2009; Pujolar et al 2006, 2007, 2009). In agreement with these observations, such a small-scale genetic patchiness of glass eel waves would result from independent mating events involving small groups of breeders separated by space or by time (Maes et al 2006; Pujolar et al 2009).…”
Section: Introductionmentioning
confidence: 97%